Pengaruh Kecepatan Udara Terhadap Performa Crassdraft Gasifier Dengan Bahan Bakar Serutan Kayu Jati - Abrori, Syafiq; , Nur Aklis, ST, M. Eng (2016)
Fossil fuels are natural resources that are not renewable, to cope with future energy crisis several alternative sources of energy sources started to be developed one biomass energy. Biomass in energy production industry, refers to biological material living or recently dead that can be used as fuel or for industrial production Gasification is a process that uses heat to transform solid biomass or solid carbonaceous other into synthetic gas such as natural gas that has been burned, through our usual gasification change almost all of the solid organic materials into clean fuel gas. In this study begins by modifying the airways in the reactor, then the supply of air from the blower speed is varied. Air speed used is 3 m / s, 3.5 m / s and 4 m / s, then measured the combustion temperature and the temperature of boiling water every 1 minute. The results of a comparison study combustion temperature at a speed of 3 m / s, 3.5 m / s, 4 m / s. From the pictures look old flame of the most effective is to use a variation of air velocity of 3 m / s ie for 17 minutes, the speed of 3.5 m / s for 15 minutes, and a speed of 4 m / s for 14 minutes. Combustion temperatures highest in the experiment using a speed of 3 m / s, in the 7th minute, with the temperature 700.66 ℃, to the speed of 3.5 m / s in the 7th minute of 718.33 ℃, and at a speed of 4 m / s on a minute -4 amounted to 644.16 ℃. From a comparison between the temperature of combustion speed of 3 m / s, 3.5 m / s and 4 m / s indicates the lowest speed will produce effective flame longer, while using the air velocity will be obtained most large combustion temperature. This happens as long as the stoichiometric limits of course.